THE SPECIFICITIES OF TREATMENT TO JUDGE SHORT CONVICTIONS IN THE REPUBLIC OF KOSOVO - Hoxha, Resmi (European Scientific Journal, ESJ, 2015)
The Republic of Kosovo, although new to citizenship, in terms of legislation and penal institutions has a very interesting course, which itself includes acts and institutions within the former Yugoslavia, Serbia, UN Protectorate and finally after independence through legislation and institutions of the Republic of Kosovo. After the war ended in 1999, in Kosovo there was a mix of legal acts of the former Yugoslavia and acts issued by UNMIK. Now, five years after the declaration of independence, Kosovo has pledged to follow its path towards the EU which has led to legislation in Kosovo to develop rapidly in order to meet international standards for accession to the EU and other international structures. The new system Kosovo criminal convictions are considered short sentences that can be imposed for a period of 30 days beyond the six (6) months for the criminal offense and punishable by three years in prison for offenses of a minor. In accordance with the legal infrastructure, in the Republic of Kosovo, the Kosovo Correctional Service, since 2009, has a special institution holding short sentences, and this institution is Correctional Center for Smrekonica short sentences, an institution which meets requirements and international standards for accommodation, treatment and socialization of persons sentenced to short prison sentences. Our experience gives us the right and opportunity to be determined for full justification sentencing brief prison sentence of imprisonment are kept in special institutions half-open or open like that Correctional Center for shorter sentences Smrekonica. This facility provides the opportunity for an adequate treatment, constructive convicts, provides adequate treatment for execution of sentence and creates the right atmosphere treatment. The possibility of employment in the economy of the institution and engaging in Offender out for the needs of different organizations, contributes to prisoners in psychic terms more easily afford the sentence and opportunities negative impact on each other inmates are small me. Characteristic is the fact that over 85% of prisoners with short sentences are not employed but live together with parents and are economically dependent on their parents. This fact is of concern to society and the state of Kosovo, which is most essential in this regard state bodies to take concrete measures for the employment of citizens of Kosovo and in particular the hiring of new generations.